Atmospheric degradation of 2- nitrobenzaldehyde: Photolysis and reaction with OH radicals. (December 2017) - Bouya, H.; Al Rashidi, M.; Roth, E.; Salghi, R.; Chakir, A.
Abstract: This work presents an experimental study of the gas phase kinetics of 2-nitrobenzaldehyde (2-NBA) photolysis and oxidation by OH radicals. The experiments were carried out in an atmospheric simulation chamber coupled to an FTIR spectrometer and CG/MS. The UV spectra of 2-NBA were also measured and the experimentally determined absorption cross sections were used to estimate the atmospheric photo-dissociation constant of 2-NBA with a global quantum yield of 0.5. The obtained results indicate that 2-NBA is a highly photolysable. A mechanism of 2-NBA photolysis was proposed based on the identification of photolysis degradation products. The kinetics of oxidation of 2-NBA by OH radicals was investigated over the temperature range 308–352 K. The obtained rate coefficients exhibits slight negative temperature dependence and the Arrhenius expression obtained is as follows: kOH+2-NBA (T)= (7.00 ± 3.40) × 10 −12 exp (577 ± 156/T) cm 3 molecule −1 s −1 . The calculated rate coefficients lead to tropospheric lifetimes of 2-NBA that are in the order of a few minutes, relative to photolysis, or a few hours, relative to oxidation by OH radicals. Graphical abstract: Highlights: The UV absorption of 2-nitrobenzaldehyde (2-NBA), in gas phase, have been measured. This work provides the kinetic of the photolysis and OH reaction of 2-NBA. A possible degradation products for photolysis of 2-NBA were identified. The kinetic study with OH was carried out over the temperature range 308–352 K. The tropospheric lifetimes of this compound is estimated.